Breeds and muscle types modulate performance of near-infrared reflectance spectroscopy to predict the fatty acid composition of bovine meat. (January 2015) - Mourot, B.P.; Gruffat, D.; Durand, D.; Chesneau, G.; Mairesse, G.; Andueza, D.
Abstract: This study aimsto assess near-infrared reflectance spectroscopy feasibility for predicting beef fatty acid (FA) composition. Experimental scheme included four breeds (Angus, Blond d'Aquitaine, Charolais, Limousin) and three muscles, Longissimus thoracis (LT), Rectus abdominis (RA), Semitendinosus (ST). The results showed that 1) increasing FA content variability with several breeds increased calibration model reliability (R 2 CV>0.86) for the major individual and groups of FA unless polyunsaturated FAs, 2) Longissimus thoracis FAs were better predicted than RA FAs while no ST FAs were correctly predicted (R 2 CV<0.71). This difference could be explained by FA content, FA variability or specific muscle physico-chemical characteristics. Highlights: NIRS was tested to predict beef fatty acid composition. Using several breeds increases fatty acid variability and prediction ability. Fatty acid prediction varies according to the muscle used. For an industrial use, Rectus abdominis muscle is recommended for NIRS analyses.